Pengaruh Team Building Dalam Meningkatkan Kohesivitas Team Kerja - Amalia, Nur Riza (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
This research aims to see whether there is an influence of team building in increasing work team cohesiveness among company A company needs things that can make human resources work optimally. Employees in a company must work together to achieve targets in their work, which requires cohesiveness within a team. The research method used was a combination of qualitative and quantitative with an indoor outbound training intervention method and used a quasi-experimental design. The results show that there is no influence of team building on work team cohesiveness at PT. X.